2022
DOI: 10.1097/corr.0000000000002420
|View full text |Cite
|
Sign up to set email alerts
|

Does Military High-speed Boat Slamming Cause Severe Injuries and Disability?

Abstract: Background Many operators of professional high-speed boats suffer severe, acute, and permanent injuries caused by slamming-induced hull impacts. As the number of professional high-speed boats and their speed capabilities increase, operators are reporting increasing numbers and severity of injuries. However, the actual incidence rate of acute injuries and the prevalence of chronic musculoskeletal disorders are still unknown. Questions/purposes We sought to investigate, among professional high-speed boat operato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The higher rate of chronic pain and pain medication reported by Ullman et al. 18 may be because of their older study population compared to the cohorts studied by de Alwis et al. 16 and Hurpin et al.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The higher rate of chronic pain and pain medication reported by Ullman et al. 18 may be because of their older study population compared to the cohorts studied by de Alwis et al. 16 and Hurpin et al.…”
Section: Resultsmentioning
confidence: 79%
“…The anecdotal reports and retrospective survey data indicate that there appears to be a chronic injury issue post-service career but do not identify what specific characteristics of exposures are injurious. 3 , 8 This limitation drives the need for regular measurement of routine transit accelerations with accompanying during and post-transit monitoring of pain and soreness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, current information is not enough to provide a general view of how much other directions of vibration could affect human safety. However, Ullman et al's [6] survey indicated that most of the human injuries occurred during the impact shock, which contained fore-and-aft and lateral accelerations.…”
Section: Safety Evaluations Of Hspcsmentioning
confidence: 99%
“…According to Figure 1, before 1992, safety on board HSPCs was not given as much attention, while the number of publications indicates an upward trend with time. Considering various reports of health risks on board these vessels [4][5][6], this upward trend demonstrates the increasing importance of the safety improvements of HSPCs.…”
Section: Introductionmentioning
confidence: 99%